The life and times of Persimmon Wilson [large type] - Peacock, Nancy (Thorndike Press, 2017)
A slave-turned-Comanche warrior travels from the brutality of a New Orleans sugar cane plantation to the indomitable frontier of untamed Texas to search for the woman he loves and for his own identity.